Optimizing Social Media in Building School Existence (Study on Instagram account @man1palembang.official) - Gerry Devara; Eraskaita Ginting; Badarudin Azarkasyi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to explain the form of social media optimization of Instagram MAN 1 Palembang in building its existence. The method used is a qualitative method with a descriptive approach and uses Media Ecology theory. The research involved five informants consisting of the vice principal for public relations, Instagram management admins, teachers, OSIM members, and students. The results of the study show that the optimization of Instagram social media @man1palembang.official Instagram account has been optimal in building the existence of Madrasah Aliyah Negeri 1 Palembang. This is shown by the increase in prospective registrations by new students, the number of impressions on posts and Instagram followers. Through various efforts in channeling effective communication, presenting interesting and relevant content, responsive interaction with the audience, both interactions in post comments and DMs (Direct Messages), and planned content management, Instagram MAN 1 Palembang has succeeded in building its existence